DEVELOPMENT OF GLOBALLY DISTRIBUTED COMPUTING INFRASTRUCTURES - YASINSKIIY, ANDRIY; SOLOVEІ LIUDMYLA; HRYSYUK, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Distributed computing systems are a modern trend in the development of computer technologies caused by the development of computing power and the expansion of global network services. GRID technology is designed to provide flexible, secure and coordinated shared access to resources. The article discusses the characteristics of distributed computing infrastructures. The concepts of "distributed computing" and "GRID technology" have been clarified. A comparison and analysis of the capabilities of distributed technologies, types of GRID systems, as a means of sharing resources was performed; directions for further research, use, development and implementation. The main idea behind the development of GRID technology is to combine network resources and obtain a metacomputer, users of such a virtual environment manage the information processing process from a personal computer. Successfully deployed, in many countries of the world, and implemented projects with the use of Grid technologies have shown its perspective. Modern Grid projects described in the literature allow to "virtualize" computing resources and provide the user with a system that "encapsulates" (hides) the details of its implementation. Prospects for creating GRID systems in Ukraine and the world are considered. Ukrainian scientists took the first steps in the development of Grid technologies together with their European colleagues. The implementation of Grid-systems in the practice of scientific research, the organization and implementation of complex technological calculations, the processing of large data sets for the formation of management decisions will require appropriate specialists.